2021
DOI: 10.1186/s12893-021-01191-6
|View full text |Cite
|
Sign up to set email alerts
|

ICG fluorescence imaging in colorectal surgery: a snapshot from the ICRAL study group

Abstract: Background Fluorescence-guided visualization is a recently proposed technology in colorectal surgery. Possible uses include evaluating perfusion, navigating lymph nodes and searching for hepatic metastases and peritoneal spread. Despite the absence of high-level evidence, this technique has gained considerable popularity among colorectal surgeons due to its significant reliability, safety, ease of use and relatively low cost. However, the actual use of this technique in daily clinical practice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“… 32 , 33 Uptake by colorectal surgeons in our study is consistent with rates recently reported by Italian surgeons. 34 In contrast rates for ICG use amongst bariatric, foregut, and thoracic surgeons has not previously been reported, yet the increased use amongst those specialties is not surprising given the evolving literature in the respective disciplines. More frequent use amongst foregut, thoracic, and bariatric surgeons is in keeping with ease of NIRFI integration into their surgical techniques due to a high volume of laparoscopic procedures enabling routine access to NIRFI equipment.…”
Section: Discussionmentioning
confidence: 98%
“… 32 , 33 Uptake by colorectal surgeons in our study is consistent with rates recently reported by Italian surgeons. 34 In contrast rates for ICG use amongst bariatric, foregut, and thoracic surgeons has not previously been reported, yet the increased use amongst those specialties is not surprising given the evolving literature in the respective disciplines. More frequent use amongst foregut, thoracic, and bariatric surgeons is in keeping with ease of NIRFI integration into their surgical techniques due to a high volume of laparoscopic procedures enabling routine access to NIRFI equipment.…”
Section: Discussionmentioning
confidence: 98%
“…The success stories in the field of image-guided surgery are based on technologies that maximally align with innovations made in other fields. For example, initial work on fluorescence laparoscopy presented in prostate cancer surgery [ 195 ] was later transferred to breast surgery [ 196 ] and the technique is now also implemented during i.e., laparoscopic colorectal surgery [ 94 , 197 ]. Such knowledge sharing can be considered highly valuable as it helps boost innovation across disciplines.…”
Section: Future Prospectsmentioning
confidence: 99%
“…It allows intraoperative real-time assessment of the blood supply to the stumps of the large intestine after resection and to the intestine after anastomosis [ 2 ]. Good blood supply to the anastomosis is crucial for proper healing and preventing intestinal anastomotic leak [ 3 ].…”
Section: Introductionmentioning
confidence: 99%